KETERBATASAN SOAL PILIHAN GANDA DALAM MENGUKUR PEMAHAMAN HISTORIS SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) DI SMA AL ISLAM JAMSAREN - Dini Luthfiyya Maajida; Muhammad Irwansyah; Shoimatul Rahma Fauziyah; Aqilla Fadia Hayya Anwar; Muhammad Hafidz Abdur Rosyid (Jurnal Pustaka Cendekia Pendidikan, 2026)
Learning evaluation is an important part of determining the achievement of learning objectives, including in the subject of Islamic Cultural History (Sejarah Kebudayaan Islam/SKI). Multiple-choice questions are often used because they are practical and efficient; however, this instrument has limitations in measuring students’ historical understanding in depth. This study aims to analyze the limitations of multiple-choice questions in measuring students’ historical understanding in SKI learning at SMA Al Islam Jamsaren. This research employed a descriptive qualitative approach with data collected through interviews with SKI teachers and students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that multiple-choice questions are effective for measuring general mastery of learning materials because they are easy to implement and assess. However, this instrument is less effective in exploring students’ analytical skills, critical thinking, and deeper understanding of historical events. Therefore, multiple-choice questions need to be complemented with other evaluation methods, such as essays, discussions, and presentations, to obtain a more comprehensive measurement of students’ historical understanding. Keywords: learning evaluation, multiple-choice questions, historical understanding, Islamic Cultural History, assessment instruments